New Plants for Florida: Grape - Richard L. Jones; Mary Duryea; Berry J. Treat (EDIS)
Until the 1980s, nearly all research effort was focused on development of disease-resistant bunch grape varieties. In the late 1970s, muscadine breeding began to be emphasized. Developments of biotechnological procedures to facilitate genetic improvement of grape began at the Leesburg site in 1984 and continue at Apopka, Florida. The program has been responsible for a number of pivotal technological advances for grape and has been awarded two U.S. patents for work in genetic transformation. This document is part of Circular 1440, a publication of the Florida Agricultural Experiment Station, the Agronomy Department and IFAS Communication Services, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date August 2003. Originally published as a booklet by IFAS Communication Services June 2003.